The peculiarity of metaphor in the work of Khurshid Davron - Kurbanova Muharram; S.M.Umirova (Zien Journals, 2022)
This article explains the elements of language in Uzbek linguistics, syntactic figures and their importance in the literature. At the same time, while analyzing the relationship between language and literature, the revelation of the human psyche using language phenomena is explored.
Keywords: metaphor; poetics; Aristotle; lingvopoetics